Assessing Caesarean Section rates using the Robson Ten Group classification system in the western rural center of Nepal - Basnyat, Subi; Shah, Rajiv; Baral, Gehanath; Khapung, Robin; Gurung, Sonam; Bhandari, Jeetendra; K.C, Kiran (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Rising caesarean sections (CS) have been a global concern. The World Health Organization, as a global standard for assessing, monitoring, and comparing the caesarean rate, has adopted the Robson or ten-group classification system. The study aimed to know the caesarean section rate in Karnali Academy of Health Sciences(KAHS) using the Ten Group Classification System, or Robson Classification, and evaluate major contributing group to overall caesarean rate.Methods: This was a hospital-based retrospective study conducted in KAHS, Nepal, from April 2022 to March 2023. The population data were retrieved from the maternity ward and classified using the Ten Group classification system. The overall caesarean rate, the largest population group, the caesarean section rate in each group, and the primary and least contributing groups were analysed. Results: The total number of deliveries during the study period was 505, with a caesarean section rate of 16.4%. The highest delivery population was in group 1, 174 (34.4%), followed by group 3, 143 (28.3%). The significant contribution to the CS rate was from group 5 (88.2%). All women with a single pregnancy with a transverse or oblique lie, including those with a previous caesarean section in Group 9, had 100%, but all the deliveries by convention were caesarean.Conclusion: The classification has effectively identified the group with a large number in delivery and also has identified the major contributing group. This has provided a clear depiction of the need for strategic intervention, mapping institutional policies and effective clinical decision-making to optimize the caesarean rate.